Practical primer: a cave management system for safe and successful mining - Parsons, J; Davenport, K; Thomas, A; Jakubec, J (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining methods are among the most complex mining techniques used in the mining industry today, owing to their large scales, strong interdependence of geotechnical conditions and operational practices, and presence of caving-specific hazards. Challenges are further amplified as operations move to greater depths with higher stresses and increased geotechnical and operational risks. Despite these challenges, companies are increasingly turning to caving methods due to their capacity for high-tonnage, low-cost production from large underground orebodies. These organisations must learn to manage the complexities of cave mining, often with minimal institutional caving experience. A strong cave management system is fundamental for the safe, successful and profitable extraction of planned reserves through all stages of caving. These systems integrate cave design and governance protocol with responsive hazard-specific management plans and performance monitoring programs (e.g. inrush, airblast, seismic hazard and subsidence) to guide mine operations and control risks. This paper outlines an experience-based management plan framework, including typical components, key considerations and performance metrics, which may be adopted by caving operations as a foundation for successful cave execution.
Keywords: cave management